The coding of migration status in English General Practice data from 2011 to 2024 - Boukari, Yamina; Hiam, Lucinda; Scuffell, Jamie; Burns, Rachel; Tamborska, Arina; Wiedemann, Milan (International Journal of Population Data Science, 2025)
Objectives Migration status is a determinant of health, but it is not routinely recorded in General Practice (GP) records. We explored the recording of migration-related SNOMED-CT codes (a structured clinical vocabulary used in GP records) over time in order to inform future research on migrants’ health using GP data. Method We used NHS England’s SNOMED Code Usage in Primary Care datasets from 2011/12 to 2023/24 within the opencodes R package to describe the use of SNOMED-CT codes relevant to migration. Codes were grouped into five codelists: 1) all migration-related codes, 2) country-of-birth codes, 3) immigration-legal-status codes, 4) asylum or refugee codes or 5) interpreter-related codes. We calculated the total and annual counts of recorded instances of any code within each codelist and for all SNOMED-CT codes and the annual percentages of migration-related codes compared to all SNOMED-CT code usage. Results From 2011/12 to 2023/24, there were over 30 million instances of 1118 migration-related SNOMED-CT codes being recorded in GP records. Migration coding increased over time, with a particularly sharp increase during the COVID-19 period. Whilst we also observed a similar trend for overall SNOMED-CT coding, the percentage of migration coding compared to overall SNOMED-CT code usage increased from 0.067% in 2011/12 to 0.082% in 2023/24. The most commonly recorded codes indicated the need for an interpreter and a main spoken language of Polish, Romanian or Urdu. Amongst all uses of country-of-birth codes, the five most common were India, Pakistan, Romania, Nigeria and China. The most common legal status codes were related to asylum or refugee status. Conclusion Migration coding has improved over time, particularly following COVID-19, indicating the feasibility of using GP records to research the health of migrants in England. However, there may be biases in the types of migrants who are coded by GP staff, which is important to consider when interpreting results.